2021
DOI: 10.5194/acp-21-3919-2021
|View full text |Cite
|
Sign up to set email alerts
|

Meteorology-driven variability of air pollution (PM<sub>1</sub>) revealed with explainable machine learning

Abstract: Abstract. Air pollution, in particular high concentrations of particulate matter smaller than 1 µm in diameter (PM1), continues to be a major health problem, and meteorology is known to substantially influence atmospheric PM concentrations. However, the scientific understanding of the ways in which complex interactions of meteorological factors lead to high-pollution episodes is inconclusive. In this study, a novel, data-driven approach based on empirical relationships is used to characterize and better unders… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 88 publications
0
35
0
Order By: Relevance
“…A positive SHAP value means that the prediction (PM 2.5 ) based on the corresponding influencing factor is above the mean value (the average PM 2.5 ). The relative importance of each variable is represented by their mean absolute SHAP values [52]. Advantages of the SHAP algorithm include: (1) global interpretabilitythe collective SHAP value can identify positive or negative relationships for each variable, and the global importance of different features can be calculated by computing their respective absolute SHAP values; (2) local interpretability-each feature acquires its own corresponding spatial SHAP value in different locations; this resolves the limitation of traditional methods of evaluating relative importance whereby results are obtained across the entire region or population but not for each pixel and individual [53].…”
Section: Shapley Additive Explanation (Shap)mentioning
confidence: 99%
“…A positive SHAP value means that the prediction (PM 2.5 ) based on the corresponding influencing factor is above the mean value (the average PM 2.5 ). The relative importance of each variable is represented by their mean absolute SHAP values [52]. Advantages of the SHAP algorithm include: (1) global interpretabilitythe collective SHAP value can identify positive or negative relationships for each variable, and the global importance of different features can be calculated by computing their respective absolute SHAP values; (2) local interpretability-each feature acquires its own corresponding spatial SHAP value in different locations; this resolves the limitation of traditional methods of evaluating relative importance whereby results are obtained across the entire region or population but not for each pixel and individual [53].…”
Section: Shapley Additive Explanation (Shap)mentioning
confidence: 99%
“…15). This implies that emissions are the source of haze over the NCP, and meteorological factors worsen haze (e.g., Wang et al, 2015;Stirnberg et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These haze events are caused by emissions of pollutants combined with unfavorable meteorological conditions (Yang et al, 2016;Cai et al, 2017;Zhang et al, 2021). Although emissions play an important role in the generation of haze, numerous studies have suggested that meteorology is also a significant factor in the occurrence of extreme haze events (Quan et al 2011;Wang et al 2015;Gao et al 2016;Stirnberg et al, 2021). For instance, Dang and Liao (2019) found that large interannual variations in the frequency and intensity of severe winter haze days were driven mainly by changes in meteorology.…”
Section: Introductionmentioning
confidence: 99%
“…Toms et al (2020) further explored how two different methods, layerwise relevance propagation and backward optimization, can be used to glean scientifically relevant information from neural network predictions of variability in the Earth System. Stirnberg et al (2021) use an alternative method, SHapley Additive exPlanations (SHAP) applied to boosted regression trees, to quantify the importance of various meteorological drivers on particulate matter concentrations.…”
mentioning
confidence: 99%